2012
DOI: 10.1007/s10903-012-9597-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors Associated with the Knowledge About HIV of the Immigrants from China, Latin America, the Maghreb and Senegal in the Basque Country (Spain)

Abstract: The objective of this study was to identify the social factors that explain the differences in knowledge with regards to HIV/AIDS among immigrants in the Basque Country (Spain). We conducted a cross-sectional study based on information obtained in the Basque Health Survey for 754 immigrants from: 86 China, 368 Latin America, 237 the Maghreb and 74 Senegal. Odds ratios (95% CI) were calculated from logistic regression models to measure the degree of association between inadequate knowledge regarding transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Our findings revealed that the higher socioeconomic status of the study participants, such as having education, professional status and internet use appeared as the predictors of HIV/STI knowledge which is in line with other studies. 38,40,41 This study also aimed to examine the relative predictive strength of socio-demographic factors, media use-related factors, and utilization of communication activities-related variables in determining STI/HIV knowledge among Rohingya refugee women. The R 2 value indicated that the utilization of communi-cation activities emerged as a stronger predictor of good STI/HIV knowledge compared to socio-demographic variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings revealed that the higher socioeconomic status of the study participants, such as having education, professional status and internet use appeared as the predictors of HIV/STI knowledge which is in line with other studies. 38,40,41 This study also aimed to examine the relative predictive strength of socio-demographic factors, media use-related factors, and utilization of communication activities-related variables in determining STI/HIV knowledge among Rohingya refugee women. The R 2 value indicated that the utilization of communi-cation activities emerged as a stronger predictor of good STI/HIV knowledge compared to socio-demographic variables.…”
Section: Discussionmentioning
confidence: 99%
“…Rodríguez-Álvarez et al argued that inadequate knowledge about HIV is associated with various social factors such as place of birth, education level, and immigration status. 38 The authors suggest that initiatives are Within this densely populated refugee setting, the risk of abuse and the prevalence of diseases such as sexually transmitted infections (STIs) are significantly high. Several factors contribute to this situation, including an escalation in genderbased sexual violence and exploitation, [10][11][12][13][14] insufficient information regarding STIs, 13 disrupted healthcare services and limited access to STI/HIV prevention and treatment, [15][16][17] inadequate availability of condoms and other preventive tools, [18][19][20] stigma and discrimination, 19 unsafe sexual practices, and limited access to diagnostic and treatment facilities for STIs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation